2007
DOI: 10.1242/dev.02871
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin sulfate glycosaminoglycans control proliferation, radial glia cell differentiation and neurogenesis in neural stem/progenitor cells

Abstract: Although the local environment is known to regulate neural stem cell (NSC) maintenance in the central nervous system, little is known about the molecular identity of the signals involved. Chondroitin sulfate proteoglycans (CSPGs) are enriched in the growth environment of NSCs both during development and in the adult NSC niche. In order to gather insight into potential biological roles of CSPGs for NSCs, the enzyme chondroitinase ABC (ChABC) was used to selectively degrade the CSPG glycosaminoglycans. When NSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
157
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(171 citation statements)
references
References 71 publications
12
157
0
2
Order By: Relevance
“…We believe that Tnc and other ECM molecules promote the timely transition from an early into a late NPC. Along these lines, we recently showed that interference with glycosaminoglycan biology strongly affects cortical NPC maturation (Sirko et al, 2010;Sirko et al, 2007). In the spinal cord, the loss of Tnc leads to a sustained FGF-dependent proliferation and delayed EGF-dependent migration of immature astrocytes caused by reduced FGF signalling levels, most probably resulting from an upregulation of Sulf1.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…We believe that Tnc and other ECM molecules promote the timely transition from an early into a late NPC. Along these lines, we recently showed that interference with glycosaminoglycan biology strongly affects cortical NPC maturation (Sirko et al, 2010;Sirko et al, 2007). In the spinal cord, the loss of Tnc leads to a sustained FGF-dependent proliferation and delayed EGF-dependent migration of immature astrocytes caused by reduced FGF signalling levels, most probably resulting from an upregulation of Sulf1.…”
Section: Research Articlementioning
confidence: 99%
“…Our laboratory has contributed to the understanding of extracellular matrix (ECM) molecules for the regulation of NPC behaviour (Czopka et al, 2010;Czopka et al, 2009;Garwood et al, 2004;Sirko et al, 2009;Sirko et al, 2010;Sirko et al, 2007;von Holst et al, 2007;von Holst et al, 2006). One particular ECM molecule is the glycoprotein tenascin C. (In this article, Tnc refers to the gene or the mRNA and Tnc refers to the protein or to general statements.)…”
Section: Introductionmentioning
confidence: 99%
“…CSs and DSs have important roles in neural precursor proliferation, neuronal differentiation, migration and neuroprotection (Sato et al, 2008;Sirko et al, 2007;Sugahara and Mikami, 2007;von Holst et al, 2006). Previous studies indicated that the functions of CSs and DSs on NSCs are determined by their sulfation patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this proteoglycan is present in several other NSC microenvironments where it was suggested for NSC survival and the maintenance of their niches [84,[125][126][127]. The rhombomere-exclusive expression of the cell surface glycoconjugate Hnk-1 may also contribute to the establishment of Sox2 negative/positive zones in the hindbrain, as in the spinal cord inhibition of Sox2 that led to ectopic expression of Hnk-1 [56].…”
Section: Discussionmentioning
confidence: 99%